His baby no matter what - Senate, Melissa (Senate, Melissa. Dawson family ranch., 2021)
"Nothing will change how much Colt Dawson loves his baby boy. Not even the shocking news his deceased wife lied about Ryder's paternity. But confronting Ava Guthrie about his ex's sperm-donor scheme doesn't go as planned. For starters, Ava needs his help rescuing her alpaca farm. And second, she's everything his late wife wasn't. Genuine. Kind. Utterly captivating. Will Ava heal Colt's betrayed heart in time for a Wyoming family Christmas?" --